Morphology and Composition of Brake Wear Particles Ameliorated by an Alumina Coating Approach - Ran Cai; Jingzeng Zhang; Xueyuan Nie (Chemistry)
A plasma-assisted electrochemical deposition (PAECD) technology was introduced to coat a cast iron brake disc for the possible reduction of brake wear and brake wear particle (BWP) emission. The majority of the coating consisted of alumina (Al2O3), determined by energy dispersive X-ray (EDX) analysis and X-ray diffraction (XRD) analysis. To validate the above strategy of the coating technology for automotive brake corners, one brake stock rotor was replaced by a PAECD-coated rotor for a vehicle road test. After the road test, weight loss of the brake components (rotors and pads) was measured, showing that the alumina coating can reduce the brake wear by more than 70%. BWPs were also collected from wheel barrels, spokes, and brake friction rings of the coated and uncoated rotors during the road test. A morphology and chemical composition analysis of the collected BWPs indicated that the coating could reduce BWP generation from the original sources and avoid a metal pick-up (MPU) issue, leading to less metallic content in BWPs. This alumina coating may provide the auto sector with a sustainable approach to overcome the brake dust emission problem, evidenced by less wear of the brake pads, minimal wear of the coated brake rotor, less MPUs, and a clean wheel rim on the coated brake corner.